INOVASI PENDIDIKAN DI ERA DIGITAL: PERAN MEDIA PEMBELAJARAN DIGITAL DALAM MENINGKATKAN KUALITAS BELAJAR - Heraldi, Bernaditus; Dwi Badzlina, Ulya; Fitriyana Pratiwi, Nur; Supriyadi; Setya Hermawan, Jody (Universitas Negeri Medan, 2024)
Abstract: The rapid development of digital technology has brought significant changes in various aspects of life, including the world of education. The use of digital learning media is increasingly widespread and is expected to improve the quality of student learning. This study aims to comprehensively examine the role of digital learning media in improving the quality of student learning. Through a literature study, this study analyzes various relevant literature to identify types of effective digital learning media, factors that influence the success of their use, and their impact on student learning outcomes. The results of the study indicate that digital learning media has great potential to increase learning motivation, learning interactivity, and access to learning resources. However, the success of utilizing digital learning media is also influenced by several factors, such as the quality of media design, teacher support, and infrastructure readiness. This study concludes that the integration of digital learning media in the learning process needs to be carried out in a planned and systematic manner to achieve optimal results. Keyword: Innovation, Digital Technology, Learning Media Abstrak: Perkembangan teknologi digital yang pesat telah membawa perubahan signifikan dalam berbagai aspek kehidupan, termasuk dunia pendidikan. Penggunaan media pembelajaran digital semakin marak dan diharapkan dapat meningkatkan kualitas belajar siswa. Penelitian ini bertujuan untuk mengkaji secara komprehensif peran media pembelajaran digital dalam meningkatkan kualitas belajar siswa. Melalui studi pustaka, penelitian ini menganalisis berbagai literatur yang relevan untuk mengidentifikasi jenis-jenis media pembelajaran digital yang efektif, faktor-faktor yang mempengaruhi keberhasilan penggunaannya, serta dampaknya terhadap hasil belajar siswa. Hasil kajian menunjukkan bahwa media pembelajaran digital mempunyai potensi yang luar biasa untuk meningkatkan motivasi belajar, interaktivitas pembelajaran, dan akses terhadap sumber belajar. Namun, keberhasilan pemanfaatan media pembelajaran digital juga dipengaruhi oleh beberapa faktor, seperti kualitas desain media, dukungan guru, dan kesiapan infrastruktur. Penelitian ini menyimpulkan bahwa integrasi media pembelajaran digital dalam proses pembelajaran perlu dilakukan secara terencana dan sistematis untuk mencapai hasil yang optimal. Kata Kunci: Inovasi, Teknologi Digital, Media Pembelajaran